IMPLIKASI YURIDIS DAN TEOLOGIS PERPINDAHAN KEYAKINAN DALAM IKATAN PERKAWINAN : ANALISIS STATUS HUKUM PERKAWINAN PASCA MURTAD - Muslih, Muslih; Sayuti, Hendri; Haqq, Muhammad Valiyyul (Hukum Islam, 2025)
This study examines the juridical and theological implications of apostasy (conversion from Islam) within marital bonds in the Indonesian legal context through a comprehensive comparative analysis with international jurisprudence. The research aims to analyze the legal status of marriages post-apostasy by exploring the intersection between religious law principles, state legal provisions, and international human rights frameworks. Using a normative juridical approach with qualitative analysis, this study examines legal materials from 45 religious court decisions across five Indonesian provinces (2018-2023), statutory regulations, and comparative theological perspectives from scholars in the Netherlands, United Kingdom, Egypt, Turkey, and Malaysia. The findings reveal a complex legal dichotomy between theological principles that generally consider apostasy as automatically dissolving the marriage bond (fasakh) and the Indonesian positive law requiring formal judicial processes. This study identifies four distinct patterns in religious court decisions: immediate dissolution upon apostasy, conditional dissolution requiring a waiting period (iddah), maintaining the marriage's validity until formal divorce procedures, and a progressive maqasid-based approach that prioritizes human rights protection. The novelty of this research lies in its integrative framework that synthesizes classical Islamic jurisprudence with contemporary human rights discourse, demonstrating how religious courts negotiate between theological imperatives, constitutional protection of religious freedom, and emerging international standards. The research contributes to legal scholarship by proposing a reformulated legal framework based on maqasid al-shariah principles that balances religious authenticity with protection of civil rights, particularly for women and children affected by marriage dissolution due to religious conversion.